Modes of social relationships of older persons with their neighbors - Wan Ahmad, Wan Ibrahim; Ismail, Zainab (International digital organization for scientific information (IDOSI), 2014)
One of the most obvious demographic changes in Malaysia in this century is an increase in the number and proportion of older persons. This increasing, known as the aging of population, has become a trend not only in developed countries but in developing ones as well.The purpose of this article is to analyze the modes of social relationships of the older population in rural Kelantan with their neighbors. By using a combination of sociological and anthropological method, a total of 214 older persons aged 60 years and above in rural Kelantan were selected. Data gathered through face-to-face interviews and participant-observation was analyzed using descriptive approach.As all respondents in the study area live in an agricultural area which comprised of several houses and have neighbors nearby. Results of the study reveal that there are three common modes of social relationships among the elderly respondents, namely, telephone, visit and face to face relationships in certain places such as at gathering centers, night markets, or at certain parties.Respondents believed that neighbors are the main source of relationship in their lives.